(untitled) (Journal of the College of Education for Women, 2019)
Divine laws are policies that Allah runs his servants, people are different in the accord-ing to the difference of periods .Each period has its kind of conduct and furtune of kindness and their own interest . As every nation has a kind of conduct to be applicable to them even if it will be decay in the rights of the others . For this meaning it would be permitted to meet two prophets in the same period according to the difference of their interest.The prophecy of Mohamad has been demonstrated and his message was famous according to his miracles and decisive signs. And people from other religions tried to deny his message . As the Christians tried to deny his message by making nobody believe his signs and miracles .And as the Jews tried to deny his message because of their thought of referring to be abrogat-ed from other Divine Laws and changing pretexts. But some of them as Al-Shamunia referred it by intelligency and others referred it by hearing as Al-Anania . All of them disagreed with Muslims’ belief for the prophecy of Mohamed except Al-Isawia but they thought that Mo-hamad’s message espacially means Arab.All Muslims agreed about the legality to abrogate Divine Laws .So the Imam Ibn Barhan who was one of the scholars mentioned the proofs in his book (Alwusul ila Alusul). In his book cancelled the untruth allegated by Jews .Praise be to Allah and God’s blessing and peace be upon our prophet Mohamad